Pengaruh Jenis dan Konsentrasi Penstabil Terhadap Karakteristik Fisikokimia dan Nilai Kesukaan Minuman Yogurt Jeruk - Trifena Honestin; Imro’ah Ikarini; Yunimar Yunimar (UM Purwokerto Press, 2021)
Orange yogurt drink is one of the diversivication of yogurt products, but syneresis still often occurs during the storage period which can affect consumer assessments. Therefore, it is necessary to add a stabilizer to overcome this problem. The purpose of this study was to determine the effect of different types of stabilizers and the concentration level of stabilizers added to the physicochemical characteristics and preference of orange yogurt drinks. Characteristics of yogurt drinks that were observed included pH values, Total Titrated Acid/TAT, Total Dissolved Solids/TPT, vitamin C, wheying off, viscosity, and organoleptic tests which included preference for color, aroma, texture appearance and taste of orange yogurt drinks This study uses a completely randomized design (CRD) with two factors, namely the type of stabilizer (Carboxy Methyl Cellulose/CMC, pectin, gum arabic) and the concentration of stabilizer (0.01%, 0.03%, and 0.05%). The results of this study indicate that pH value of the orange yogurt drink ranged from 3.907-4.058, total soluble solids (TPT) of the orange yogurt drink was 14.350-16,367 °Brix, vitamin C content of the orange yogurt drink was between 6.453-10.560 mg/100 g, and TAT value. 6.133 – 8.067%. The treatment of different types of stabilizers affects the physicochemical characteristics of orange yogurt drinks, including the value of pH, TPT, vitamin C, TAT, wheying off and viscosity. While the treatment of different concentrations of stabilizer affects the wheying off and the viscosity of the orange yogurt drink. The results of the interaction between the type and concentration of stabilizer significantly affect the value of pH, vitamin C, TAT, wheying off, viscosity also the value of preference for color, appearance and texture of orange yogurt drink.